2023
DOI: 10.3390/ma16031057
|View full text |Cite
|
Sign up to set email alerts
|

Express Synthesis of YAG:Ce Ceramics in the High-Energy Electrons Flow Field

Abstract: YAG:Ce ceramics by the direct action of an electron beam with 1.4 MeV energy were synthesized on a mixture of a stoichiometric composition of Y, Al, and Ce oxides without adding any substances to facilitate the process. The synthesis is realized in a time less than 1 s. The main structural phase of the obtained ceramics is YAG and YAP can be additional. The luminescence characteristics of the synthesized samples, the excitation, luminescence, decay time, and pulsed cathodoluminescence spectra, are similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…This conclusion is consistent for both nanopowder-based synthesis and the synthesis from larger grain sizes. It is likely that in the region with the highest absorbed energy density [14][15][16][17][18][19][20][21], the rate of new YAG phase formation is so rapid that charged particles do not have the opportunity to leave the reactor zone before the decomposition of the initial particles occurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is consistent for both nanopowder-based synthesis and the synthesis from larger grain sizes. It is likely that in the region with the highest absorbed energy density [14][15][16][17][18][19][20][21], the rate of new YAG phase formation is so rapid that charged particles do not have the opportunity to leave the reactor zone before the decomposition of the initial particles occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that YAG:Ce ceramics can be synthesized from refractory metal oxides using a powerful electron beam without the need for additional substances to facilitate the synthesis [15,16]. These studies have demonstrated the possibility of synthesizing ceramics in times shorter than 1 s, making it a highly attractive method for synthesizing YAG:Ce phosphors.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, Shuji Nakamura of Nichia Chemical Industries invented the phosphorconverted white LED system, which first introduced yellow emitting yttrium aluminum garnet (YAG: Ce 3+ ) phosphor coated on a blue LED to the market [6][7][8]. However, the white light obtained using this method lacks red components, limiting its application in high-end indoor lighting [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, we proposed and implemented the synthesis method of YAG ceramics with activators from a mixture of Y 2 O 3 and Al 2 O 3 powders in the field of a powerful flux of high-energy electrons [18,19]. The method seems promising: the synthesis is realized in 1s, without the use of any substances facilitating the synthesis, with high productivity without the use of additional energy sources.…”
Section: Introductionmentioning
confidence: 99%